Sidekick dynamically rebalances contractile and protrusive forces to control tissue morphogenesis. - Malin, J.; Rosa Birriel, C.; Astigarraga, S.; Treisman, J.E.; Hatini, V. (Journal of Cell Biology, 2022)
Contractile actomyosin and protrusive branched F-actin networks interact in a dynamic balance, repeatedly contracting and expanding apical cell contacts to organize the epithelium of the developing fly retina. Previously we showed that the immunoglobulin superfamily protein Sidekick (Sdk) contributes to contraction by recruiting the actin binding protein Polychaetoid (Pyd) to vertices. Here we show that as tension increases during contraction, Sdk progressively accumulates at vertices, where it toggles to recruit the WAVE regulatory complex (WRC) to promote actin branching and protrusion. Sdk alternately interacts with the WRC and Pyd using the same C-terminal motif. With increasing protrusion, levels of Sdk and the WRC decrease at vertices while levels of Pyd increase paving the way for another round of contraction. Thus, by virtue of dynamic association with vertices and interchangeable associations with contractile and protrusive effectors, Sdk is central to controlling the balance between contraction and expansion that shapes this epithelium.